The role of epigenetic changes in the pathology and treatment of inherited retinal diseases - Miller, Annie L.; James, Rebekah E.; Harvey, Alan R.; Trifunović, Dragana; Carvalho, Livia S. (Frontiers in Cell and Developmental Biology, 2023)
Elucidation of the cellular changes that occur in degenerating photoreceptors of people with inherited retinal diseases (IRDs) has been a focus for many research teams, leading to numerous theories on how these changes affect the cell death process. What is clearly emerging from these studies is that there are common denominators across multiple models of IRD, regardless of the underlying genetic mutation. These common markers could open avenues for broad neuroprotective therapeutics to prevent photoreceptor loss and preserve functional vision. In recent years, the role of epigenetic modifications contributing to the pathology of IRDs has been a particular point of interest, due to many studies noting changes in these epigenetic modifications, which coincide with photoreceptor cell death. This review will discuss the two broad categories of epigenetic changes, DNA methylation and histone modifications, that have received particular attention in IRD models. We will review the altered epigenetic regulatory events that are believed to contribute to cell death in IRDs and discuss the therapeutic potential of targeting these alterations.